Molecular genetics of arrhythmogenic right ventricular cardiomyopathy in South Africa - Blanckenberg, Janine (Department of Medicine, 2014)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a heritable disorder characterised by progressive degeneration of the right ventricular myocardium, arrhythmias and an increased risk of sudden death at a young age. Fourteen chromosomal loci have been linked to ARVC and nine disease genes have been identified. Linkage analysis of a South African family was previously performed at ARVC loci 1 to 6. ARVC loci 1 to 5 were excluded as disease loci in this family based on lack of evidence for linkage. However, a peak lod score of 2.93 was obtained for the ARVC-6 locus which is highly suggestive of linkage. Subsequently another locus (ARVC-7) and five ARVC disease genes (ARVC loci 8 to 12) have been reported. The aim of this project was to identify the disease gene that causes ARVC in this family.